Rancang Bangun Aplikasi Peramalan Laba dengan Metode Kuadrat Terkecil Berbasis Android - Audrey Sugiarto; Seng Hansun (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
The advancement of technology effects in increasing competition between companies. Because of that, companies need more than just raw information, but rather some insight that can help companies to make decisions in the future regarding all the possibilities that can happen. The data that can help the company to make decisions is a forecasting earnings because it can help predict the state of the company has right now, and also can help to make a better decision in the future. Therefore, this study discusses about the design and development of forecasting earnings application using Least Squares Method which will create an equation with the formula, y = ax + b. The method will be implemented based on Android OS at PT TRI PANJI GEMILANG using data from January 2005 to December 2013 (108 months) for data forecasting, and the data used to check the error is data from January 2014 to May 2015 (17 months). Forecasting results have a mean absolute percentage error (MAPE) about 8.26%, with an accuracy of forecasting results about 91.74%. Keywords: android, forecasting, least squares method, profits